Apoptosis-inducing factor regulates skeletal muscle progenitor cell number and muscle phenotype. - Anne-Sophie Armand (Public Library of Science (PLoS), 2011)
Apoptosis Inducing Factor (AIF) is a highly conserved, ubiquitous flavoprotein localized in the mitochondrial intermembrane space. In vivo, AIF provides protection against neuronal and cardiomyocyte apoptosis induced by oxidative stress. Conversely in vitro, AIF has been demonstrated to have a pro-apoptotic role upon induction of the mitochondrial death pathway, once AIF translocates to the nucleus where it facilitates chromatin condensation and large scale DNA fragmentation. Given that the aif hypomorphic harlequin (Hq) mutant mouse model displays severe sarcopenia, we examined skeletal muscle from the aif hypomorphic mice in more detail. Adult AIF-deficient skeletal myofibers display oxidative stress and a severe form of atrophy, associated with a loss of myonuclei and a fast to slow fiber type switch, both in "slow" muscles such as soleus, as well as in "fast" muscles such as extensor digitorum longus, most likely resulting from an increase of MEF2 activity. This fiber type switch was conserved in regenerated soleus and EDL muscles of Hq mice subjected to cardiotoxin injection. In addition, muscle regeneration in soleus and EDL muscles of Hq mice was severely delayed. Freshly cultured myofibers, soleus and EDL muscle sections from Hq mice displayed a decreased satellite cell pool, which could be rescued by pretreating aif hypomorphic mice with the manganese-salen free radical scavenger EUK-8. Satellite cell activation seems to be abnormally long in Hq primary culture compared to controls. However, AIF deficiency did not affect myoblast cell proliferation and differentiation. Thus, AIF protects skeletal muscles against oxidative stress-induced damage probably by protecting satellite cells against oxidative stress and maintaining skeletal muscle stem cell number and activation.